A Highly Active Ylide‐Functionalized Phosphine for Palladium‐Catalyzed Aminations of Aryl Chlorides. Issue 10 (2nd January 2019) - Weber, Philip; Scherpf, Thorsten; Rodstein, Ilja; Lichte, Dominik; Scharf, Lennart T.; Gooßen, Lukas J.; Gessner, Viktoria H.
Abstract: Ylide‐functionalized phosphine ligands (YPhos) were rationally designed to fit the requirements of Buchwald–Hartwig aminations at room temperature. This ligand class combines a strong electron‐donating ability comparable to NHC ligands with high steric demand similar to biaryl phosphines. The active Pd species are stabilized by agostic C−H⋅⋅⋅Pd rather than by Pd–arene interactions. The practical advantage of YPhos ligands arises from their easy and scalable synthesis from widely available, inexpensive starting materials. Benchmark studies showed that YPhos‐Pd complexes are superior to the best‐known phosphine ligands in room‐temperature aminations of aryl chlorides. The utility of the catalysts was demonstrated by the synthesis of various arylamines in high yields within short reaction times. Abstract : Give a little bit : The ylide‐functionalized phosphine Cy YMe PCy2, which is easy to synthesize in few steps, shows excellent performance in a series of C−N cross coupling reactions at room temperature. This efficiency can be explained by the strong electron‐donating properties of the ligand and its unique architecture, which allows stabilization of the active Pd species through a weak C−H⋅⋅⋅Pd interaction.